Comparison of the efficacy of acupuncture-related Therapies for post-stroke motor aphasia: A Bayesian network meta-analysis - Feng, Sisi; Tang, Mingzhi; Huang, Gan; Wang, Jumei; Lv, Yulan; He, Sijin; Liu, Duo; Gu, Lihua (Frontiers in Neurology, 2022)
Background: Motor aphasia, which can affect the communication ability of patients and even triggers severe psychological disorders, is one of the common sequelae after stroke. Acupuncture (a typical complementary alternative therapy) is frequently combined with speech training (ST) to treat post-stroke motor aphasia (PSMA) and presents significant efficacy. However, the most effective acupuncture intervention is still unknown. This study aims to analyze the efficacy of several acupuncture approaches combined with ST for PSMA to identify the best intervention for clinical decision-making by using network meta-analysis (NMA). Methods: Eight major databases were searched from the time of their establishment to March 2022. Clinical efficacy rate (CER) was used as the primary outcome indicator. R software, version (4.13.0) and STATA software (version 16.0) were used to analyze the data. Results: 29 randomized controlled trials (RCTs) and 6 treatment regimens were included in this study. In the pair-wise meta-analysis, we found that the efficacy of scalp-tongue acupuncture (STA) combined with speech training (ST) (OR = 8.30 95%Credible interval (CrI): 3.87, 17. 33), tongue acupuncture (TA) combined with ST (OR = 3.95 95%CrI: 2.27, 6.89), scalp-body acupuncture (SBA) combined with ST (OR = 3.75 95%CrI: 2.26, 6.22), scalp acupuncture (SA) combined ST (OR = 2.95 95%CrI: 1.74, 5.0) and body acupuncture (BA) combined ST (OR = 2.30 95%CrI: 1.26, 4.19) were significantly superior to that of ST. In addition, the efficacy of STA + ST was significantly superior to that of SA +ST (OR = 2. 82 95% CrI: 1.24, 6.38) and BA + ST (OR = 3.61 95% CrI: 1.40, 9.29). According to the cumulative ranking curve under Surface (SUCRA), STA + ST (SUCRA = 97.9%) may be the best treatment regimen to improve the clinical outcome in PSMA patients. Conclusion: The network meta-analysis showed that scalp-tongue acupuncture combined with speech training may be the best treatment to improved CER, compared with other combination treatments. However, since the overall quality and number studies are limited, further RCTs with large sample and multicenter are needed for further validation.